Educar para no repetir el conflicto armado (2016)
The objective of this article has to do with thinking about education in Colombian post conflict. Though it is possible to make a wide speech about the war in this country, the main objective of the text is not to deepen in the causes and characteristics of the armed conflict but in the conditions of possibilities of overcoming it. This can be possible if all citizens participate in the construction of a different country. The article is explained from the statements given by the authors such as Theodor W. Adorno, Francisco Cortés Rodas y Eufrasio Guzmán, in which Education for post conflict has an overcoming importance.